2022
DOI: 10.1155/2022/6839356
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Intestinal Bacterial Substances Associated with Disease Activities in Patients with Rheumatoid Arthritis: A Cross-Sectional Clinical Study

Abstract: Intestinal bacterial compositions of rheumatoid arthritis (RA) patients have been reported to be different from those of healthy people. Dysbiosis, imbalance of the microbiota, is widely known to cause gut barrier damage, resulting in an influx of bacteria and their substances into host bloodstreams in animal studies. However, few studies have investigated the effect of bacterial substances on the pathophysiology of RA. In this study, eighty-seven active RA patients who had inadequate responses to conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…LPS, a structural component of Gram-negative bacteria, is a known pyrogenic substance and is often used to promote the development of arthritis in animal experiments [ 89 ]. Elevated serum LPS levels caused by LPS absorption from the gut to elsewhere in the body are more frequently observed in patients with RA than in healthy controls, indicating that gastrointestinal barrier damage with LPS translocation into the bloodstream may play a role in the progression of RA by promoting inflammation, which is pivotal in RA [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS, a structural component of Gram-negative bacteria, is a known pyrogenic substance and is often used to promote the development of arthritis in animal experiments [ 89 ]. Elevated serum LPS levels caused by LPS absorption from the gut to elsewhere in the body are more frequently observed in patients with RA than in healthy controls, indicating that gastrointestinal barrier damage with LPS translocation into the bloodstream may play a role in the progression of RA by promoting inflammation, which is pivotal in RA [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In RA patients, Anti-Pg-LPS IgG antibody levels were inversely correlated with activity abilities, and Serum LPS-binding protein levels were correlated with disease biomarker levels. These results suggest that substances from oral and gut microbiota may influence disease activity in RA patients [ 98 ]. Many studies have demonstrated that P. gingivalis administration exacerbated RA, whether P. gingivalis was administered before the onset of RA [ 99–102 ] or concurrently with RA [ 46 , 103 ] or after RA induction [ 102 ].…”
Section: Oral Microbiota Gut Microbiota and Systemic Diseasesmentioning
confidence: 99%
“…Evidence indicates that Porphyromonas gingivalis could be involved in RA etiology by inducing the production of ACPAs and inflammatory processes. Moreover, Porphyromonas gingivalis transmission from the oral cavity into the lumen of the intestine could be a trigger of altered gut microbial composition, leading to bacterial dysbiosis, increased intestinal barrier permeability and the subsequent translocation of viable bacteria or products of their metabolism into the bloodstream [72]. Thus, FMT might be a valuable tool to restore the perturbation.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…It is vital to take into consideration the fact that a large number of RA patients are treated with at least one DMARD at the time of the study. A recently published crosssectional clinical study declared that intestinal bacterial counts and bacteria-related markers were affected in patients treated by MTX 7.8 ± 0.3 mg/week [72]. Correspondingly, a study screening pharmaceuticals against representative bacterial isolates of the gut, including DMARDs MTX and leflunomide, revealed that MTX affected the growth of 12 bacterial species from eight genera; specifically, Bacteroides, Clostridium, Eubacterium, Lactobacillus, Roseburia, Ruminococcus, Streptococcus, Veillonella and leflunomide inhibited the growth of two genera, Dorea and Ruminococcus [74].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%